Higher Order Thinking Abilities: Critical Thinking Abilities on Science Process Skills the Subject of Elasticity and Hooke's Law - Astalini; Darmaji; Kurniawan, Dwi Agus; Husna, Sri Muslimatul (Universitas Pendidikan Ganesha, 2024)
The rapid development of the world of education requires students to have critical thinking skills and scientific process skills in order to be able to face various problems in everyday life. This study aims to analyze the effect of critical thinking skills on scientific process skills on the subject of material elasticity and Hooke's law. The type of research used in this study is associative quantitative research. The population used was all students with a sample of 30 grade XI students. The sampling technique used purposive sampling. The research instruments used were essay tests and observation sheets. The data analysis technique used was descriptive statistical tests, the assumption test was the normality test and linearity test, and the hypothesis test was a simple linear regression test. The results of the descriptive statistical test showed that the critical thinking skills of students in each State High School were different, as well as the science process skills of students in each State High School were also different. The results of the normality test showed that the data was normally distributed with sig. > 0.05, then the results of the linearity test showed linear data with sig. > 0.05, and the results of the simple linear regression test showed that there was an influence between critical thinking skills and science process skills with a sig. < 0.05. So, it can be concluded that critical thinking skills influence scientific process skills in material elasticity and Hooke's law.